Functionalized magnetic microparticle-based colorimetric platform for influenza A virus detection. (22nd September 2016) - Chen, Chaohui; Zou, Zhong; Chen, Lu; Ji, Xinghu; He, Zhike
Abstract: A colorimetric platform for influenza A virus detection was developed by using the high efficiency of enzymatic catalysis and the reduction of gold ions with hydrogen peroxide. Aptamer-functionalized magnetic microparticles were synthesized to capture the influenza A virus. This was followed by the binding of ConA-GOx-AuNPs to the H3N2 virus through the ConA-glycan interaction. The sandwich complex was subsequently dispersed in glucose solution to trigger an enzymatic reaction to produce hydrogen peroxide, which controlled the growth of gold nanoparticles and produced colored solutions. The determination of H3N2 concentration was realized by comparing the two differently colored gold nanoparticles. This method could detect the target virus as low as 11.16 μ g ml −1 . Furthermore, it opens new opportunities for sensitive and colorimetric detection of viruses and proteins.